HEPATIC ANTIOXIDANT STATUS AND HEMATOLOGICAL PARAMETERS IN AFRICAN CATFISH, CLARIAS GARIEPINUS JUVENILE EXPOSED TO SUBLETHAL CONCENTRATION OF PSYCHOTRIA MICROPHYLLA - C. D. Nwani; A. O. Nwadinigwe; P. E. Joshua; C. C. Onyeke; S. U. Ogbonna; J. A. Ukonze; S. O. O. Eze (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to determine the hepatic antioxidant responses and hematological parameters in juvenile African catfish Clarias gariepinus exposed to sublethal concentrations of Psychotria microphylla leaf extract. Based on the 96 hr LC50 value of 0.69 mg/L, two sub-lethal concentrations of 35µg/L and 69µg/L and control were selected for exposure to fish. Samples of liver and blood were taken on day 1, 5, 10, and 15 for assessment of hepatic antioxidant responses and hematological parameters, respectively. Results indicated that P. microphylla leaf extract enhanced significantly (p<0.05) levels of lipid peroxidation, superoxide dismutase, and catalase but significantly reduced (p<0.05) glutathione reductase and glutathione peroxidase activities in the liver in both concentrations of the piscicide. There was decrease in the mean values of red blood cell count, hemoglobin, packed cell volume, mean cellular hemoglobin concentration but a mixed trend in the values of white blood cell, mean cellular hemoglobin and mean cellular volume. While glucose levels increased throughout the duration of the experiment, significant decrease (p < 0.05) was observed in protein values. Psychotria microphylla should be handled with adequate precaution to avoid possible ecotoxicological risk associated with its use.
Keywords: Psychotria microphylla; Clarias gariepinus; piscicide; hematology; antioxidants; lipid peroxidation